PEMANFAATAN DATA SISTEM INFORMASI PENERIMAAN KAS PADA ASSET MANAGEMENT UNITS - Sukmawati, Yuli (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the design of cash acceptance information system by designing of AssetManagement Unit database and to find out how the utilization of data on the cash acceptance informationsystem by designing of Asset Management Unit database in the Institut Teknologi Sepuluh Nopember (ITS).The qualitative descriptive is applied as method in this research. The data collection is conducted by usingpreliminary survey and field research. The technique which is applied in order to collect the data in this researchis conducted by using observation, interview and documentation. The result of the research indicates that theasset financial SIM is an application which can perform data and information management related to thebelonged physical asset, especially in financial issues. The cash acceptance information system in the assetsmanagement units gives information which is expected to be able to assist the data utilization and themanagement decision making. The Asset acceptance SIM supports the treasurer of acceptance in monitoring thecash flow of acceptance from the assets management units. The participation of budgeting also has an influenceto the determination of service fare to the entity of UPT which exist on asset management unit. The goodcomprehension of relevan knowledge and the making of suitable service fare will play a role in determining theamount of income.Keywords: information system, cash, asset management units.